2015
DOI: 10.1890/14-0910.1
|View full text |Cite
|
Sign up to set email alerts
|

Profiling crop pollinators: life history traits predict habitat use and crop visitation by Mediterranean wild bees

Abstract: Wild pollinators, bees in particular, may greatly contribute to crop pollination and provide a safety net against declines in commercial pollinators. However, the identity, life history traits, and environmental sensitivities of main crop pollinator species.have received limited attention. These are crucial for predicting pollination services of different communities and for developing management practices that enhance crop pollinators. We sampled wild bees in three crop systems (almond, confection sunflower, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…The distance from components of semi‐natural habitat had further variable effects within the wild bee assemblage, with the smallest species (with the shortest flight ranges) being largely confined to field edges containing wild plants, while larger species being more common in field interiors, and unaffected by edge type. Notably, in a related study we found similar contrasts in edge–interior abundance patterns among the main visitors L. malachurum , L. politum and H. taeniolatus using combined net and pan trap sampling (Pisanty & Mandelik ). These contrasts likely reflect differences in foraging needs (Potts et al .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The distance from components of semi‐natural habitat had further variable effects within the wild bee assemblage, with the smallest species (with the shortest flight ranges) being largely confined to field edges containing wild plants, while larger species being more common in field interiors, and unaffected by edge type. Notably, in a related study we found similar contrasts in edge–interior abundance patterns among the main visitors L. malachurum , L. politum and H. taeniolatus using combined net and pan trap sampling (Pisanty & Mandelik ). These contrasts likely reflect differences in foraging needs (Potts et al .…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the increase in average body size in the field interior may be linked to longer flight distances from stable foraging resources (such as wild vegetation surrounding the field) covered by larger species (Greenleaf et al . ; Pisanty & Mandelik ). Although at the time of sampling there was little wild bloom in most field edges and sometimes even in the semi‐natural batha, patches of wild plants blooming outside the crop blooming season and year are important as a stable foraging resource for bees (Garibaldi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agricultural landscapes it is common that bees are most abundant in field edges [56, 57]. Field interiors often show low abundance of solitary bees, and bees foraging there may be soil-nesting bees provided locally with nests [58]. …”
Section: Discussionmentioning
confidence: 99%
“…When soil-nesting bees are limited to field edges they must fly farther distances from the nest and face more local competition with bees around the nest. In general, soil disturbance in crop fields is assumed to be too high for soil-nesting bees to survive [8385], but recent studies suggest that it is possible [58, 86] for species that nest a meter below the surface. Agricultural practices that reduce the depth of mechanical 'action' and pesticide application will benefit the survival of soil-nesting bees within fields.…”
Section: Discussionmentioning
confidence: 99%